Moisture Sorption Isotherm and Isosteric Heat of Dried Cabya (Piper retrofractum Vahl) Powder. Issue 1 (June 2020) - Hawa, L C; Aini, K N N; Maharani, D M; Susilo, B
Abstract: Cabya ( Piper retrofractum Vahl) is a widely utilized herbal plant for Indonesian traditional medicine. Up to date, the commonly applied storage method for this plant is in dried form, and makes it less effective for distribution process and less attractive for consumers preference, i.e. consumers usually prefers to consume herbal product in powdered form. In the attempt to provide an optimized storage condition of dried cabya powder, the study was conducted to analyze the sorption isotherm behavior of dried cabya powder and to obtain the fittest sorption isotherm model by comparing obtained data to five commonly used sorption isotherm models, i.e. BET, Oswin, Smith, Caurie, and GAB model. The sorption isotherm data was obtained using static gravimetric method in 24 h of interval weighing observation. Six saturated salt solution, i.e. KOH, MgCl2, KI, NaCl, KCl, and KNO3 were employed for water activity ( aw ) in the range of 0.063 - 0.936. The observation was conducted at three different temperatures, i.e. 25±2°C, 35±2°C, and 45±2°C with triplicates. The results indicated that GAB model satisfactorily describe the sorption isotherms behavior of dried cabya powder. The mathematical form of isosteric heat equation of dried cabya powder in adsorption and desorption were also presented.